Effects of Varying Levels of Dietary Protein and Energy on Growth Performance and Carcass Yield of Indigenous Chicks in Bangladesh - Yousuf Miah, Mohammad; Chowdhury, Sachchidananda Das; Bhuiyan, A.K. Fazlul Haque (Indian Journal of Animal Nutrition, 2018)
Two feeding trials were conducted on three weeks old unsexed indigenous chicks reared in confinement to determine the effects of varying levels of dietary protein and energy on their growth performance and carcass yields. For the first trial, 360 unsexed chicks were divided into four equal groups and fed control, low protein density (LPD); moderate protein density (MPD) and high protein density (HPD) diets with CP level 11.42, 19.19, 21.30 and 23.22% in the respective diet. In the second trial, 228 chicks were fed control, low nutrient density (LND), moderate nutrient density (MND) and high nutrient density (HND) diet with ME content 3100, 2400, 2600 and 2800 kcal/kg diet and the respective CP level was 11.42, 19.05, 21.22 and 23.22%. In trial 1, birds, fed HPD diet, reached the target weight (750 g) whereas the body weight in LPD and MPD groups was lower (P<0.05). Feeding HND diet had a tendency of higher breast meat and drumstick meat yields than other groups. It was, therefore, concluded that a nutrient density of 2800 ME kcal/kg and 23% CP may be suggested for indigenous chicks to obtain profitable body weight (approx. 850 g) in confinement.